Identification of Functional Domain(s) of Fibrillarin Interacted with p2 of Rice stripe virus - Luping Zheng; Jie He; Zuomei Ding; Chenlong Zhang; Ruoxue Meng (Canadian Journal of Infectious Diseases and Medical Microbiology)
p2 of Rice stripe virus may promote virus systemic infection by interacting with the full length of fibrillarin from Nicotiana benthamiana (NbFib2) in the nucleolus and cajal body (CB). NbFib2 contains three functional domains. We used yeast two-hybrid, colocalization, and bimolecular fluorescence complementation (BiFC) assays to study the interactions between p2 and the three domains of NbFib2, namely, the N-terminal fragment containing a glycine and arginine-rich (GAR) domain, the central RNA-binding domain, and the C-terminal fragment containing an α-helical domain. The results show that the N-terminal domain is indispensable for NbFib2 to localize in the nucleolus and cajal body. p2 binds all three regions of NbFib2, and they target to the nucleus but fail to the nucleolus and cajal bodies (CBs).